HUBUNGAN INDEKS MASSA TUBUH DENGAN INDEKS HOMA-IR DAN HOMA-B PADA POPULASI NORMAL - , SUSWANTO, dr. Windarwati Sp.PK(K) ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Obesity remains a significant health problem in many countries. Various studies show that the prevalences of obesity increase significantly. Obesity is asociated with type 2 diabetes mellitus by occurring insulin resistance that increase insulin secretion from pancreatic Î² cell, exhauted condition of Î² cell can lead to decrease insulin production and manifest as type 2 diabetes mellitus. Insulin resistance is determined as homeostasis assessment insulin resistance (HOMA-IR) while obesity is ditermined as body mas index (BMI). This aim of the study is to determine the correlation of Body Mass Index (BMI) and Homeostasis model assessment insulin resistance (HOMA- IR) and HOMA-B to determine function pancreatic Î² cell . This study used cross sectional design. The subjects of this study were taken from participants who followed a general check up at Dr.Sarjito Hospital Yogyakarta and signed informed consent. Data were taken from subjects by anamnesis, physical examination and laboratory examination included fasting glucose, glucose level two hours after intake 75 gram glucose, lipid profile, and insulin. The results showed HOMA-IR of obese group differed significantly (p = 0.001) from non obese group,i.e 2,52+1,69 and 1,31+0,66, respectively. The Spearman rho correlation test between BMI and HOMA-IR have a positive correlation with r = 0.615 (p = 0.001). HOMA B in obese were 120,45+68,95% vs 77,78+50,37% non obese (p=0,001). Chi square analysis showed the ratio of prevalence was 4,2. It is concluded that BMI correlates with HOMA-IR and obese subjects have four fold risk of having insulin resistance than non-obese subjects. It is suggested to carried out preventive action by examination of HOMA-IR and HOMA-B in general check-ups participants who are obese to detect the presence of insulin resistance which is one risk factor for type 2 diabetes mellitus.